Trigonometric identity
Substituting with the secant value given:
Answer:
60%
Step-by-step explanation:
73:120*100=
(72*100):120=
7200:120=60
#1) 4 weeks, $280
#2) (5, 38)
#3) (1, 3)
#4) Step 3
#5) (y+z=6)*-8
#6) 2x+2y=8
Explanation
#1) Setting them equal,
60x+40=50x+80
Subtract 50x from both sides:
60x+40-50x=50x+80-50x
10x+40=80
Subtract 40 from both sides:
10x+40-40=80-40
10x=40
Divide both sides by 10:
10x/10 = 40/10
x=4
Plugging this in to one of our equations,
60(4)+40=240+40=280
#2) Setting the equations equal to one another,
8x-2=9x-7
Subtract 8x from both sides:
8x-2-8x=9x-7-8x
-2=x-7
Add 7 to both sides:
-2+7=x-7+7
5=x
Plugging this in to the first equation,
8(5)-2=y
40-2=y
38=y
#3) Substituting our value from the second equation into the first one,
n-2+3n=10
Combining like terms,
4n-2=10
Add 2 to both sides:
4n-2+2=10+2
4n=12
Divide both sides by 4:
4n/4 = 12/4
n=3
Substitute this into the second equation:
m=3-2=1
#4) The mistake was made on Step 3; the 4 was left off when the equations were added.
#5) To eliminate y, we want the coefficients to be the same. To accomplish this, we will multiply the first equation by -8.
#6) In order to have infinitely many solutions, we want each coefficient as well as the constant to be a multiple of our equation. Multiplying the equation by 2, we get 2x+2y=8.
To find the answer:
1. Remove parenthesis by multiplying the number outside parenthesis
Answer:
undefined -6 = 6
Step-by-step explanation:
im guessing but thinking